2022
DOI: 10.7759/cureus.30476
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis Between Ultrasound and Electromyographic and Nerve Conduction Studies in Diagnosing Carpal Tunnel Syndrome (CTS): A Systematic Review and Meta-Analysis

Abstract: Carpal tunnel syndrome (CTS) is the most common upper extremity neuropathy. The disease initially manifests as a sensory disorder in the form of paresthesia, numbness, or tingling of the fingers. The diagnosis is usually made based on history and clinical symptoms, which are confirmed using nerve conduction studies (NCS) and electromyography. More recently, ultrasound has gained more use in CTS diagnosis due to its advantages, which include patients' comfort during diagnosis, better visualization of anatomy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Similar to ultrasonography, nerve conduction study and electromyography use a variety of parameters to determine whether a patient has CTS. The NCS measuring criteria include sensory amplitude, distal motor latency (DML), sensory conduction velocity (SCV), and distal sensory latency (DSL) (30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to ultrasonography, nerve conduction study and electromyography use a variety of parameters to determine whether a patient has CTS. The NCS measuring criteria include sensory amplitude, distal motor latency (DML), sensory conduction velocity (SCV), and distal sensory latency (DSL) (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Electrodiagnostic procedures, including electromyography, are uncomfortable and painful for the patient. Nonetheless, the discomforts associated with electrodiagnostic testing are frequently disregarded (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, nerve conduction studies were the gold standard for further workup of CTS; however, more recently neuromuscular ultrasound has been shown as a validated tool in this workup with comparable sensitivity and specificity. 10 In this uncommon demographic of patients presenting with CTS, NMUS may have a unique use in identifying underlying pathology and surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…Filho(de Jesus Filho et al, 2014) conducted a cross-sectional study and reported that electrophysiological examinations had higher sensitivity than ultrasound and physical tests. Zaki(Zaki et al, 2022) reported a higher sensitivity and speci city of electromyography than that of ultrasound. Kele(Kele et al, 2003) reported a sensitivity of 90% in 77 cases.…”
mentioning
confidence: 99%